2014
DOI: 10.1186/1475-2840-13-80
|View full text |Cite
|
Sign up to set email alerts
|

Atherogenic, fibrotic and glucose utilising actions of glucokinase activators on vascular endothelium and smooth muscle

Abstract: BackgroundPharmaceutical interventions for diabetes aim to control glycaemia and to prevent the development of complications, such as cardiovascular diseases. Some anti-hyperglycaemic drugs have been found to have adverse cardiovascular effects in their own right, limiting their therapeutic role. Glucokinase activity in the pancreas is critical in enhancing insulin release in response to hyperglycaemia. Glucokinase activators (GKAs) are novel agents for diabetes which act by enhancing the formation of glucose-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 58 publications
3
16
0
Order By: Relevance
“…HF is characterized by cardiac dysfunction, increased renal vascular resistance and sodium retention. The findings that DPPIV catalytic activity, as well as its binding properties, are associated with increased sodium reabsorption [ 26 , 39 , 40 ], inflammation [ 41 , 42 , 43 ] and cardiac fibrosis [ 32 , 33 , 36 , 37 , 38 ] are consistent with the hypothesis that increased DPPIV activity plays a role in the pathophysiology of HF. In this review, we discuss how DPPIV might be involved in the cardio-renal axis of HF.…”
Section: Introductionsupporting
confidence: 67%
See 3 more Smart Citations
“…HF is characterized by cardiac dysfunction, increased renal vascular resistance and sodium retention. The findings that DPPIV catalytic activity, as well as its binding properties, are associated with increased sodium reabsorption [ 26 , 39 , 40 ], inflammation [ 41 , 42 , 43 ] and cardiac fibrosis [ 32 , 33 , 36 , 37 , 38 ] are consistent with the hypothesis that increased DPPIV activity plays a role in the pathophysiology of HF. In this review, we discuss how DPPIV might be involved in the cardio-renal axis of HF.…”
Section: Introductionsupporting
confidence: 67%
“…In addition, most peptides inactivated by DPPIV display beneficial cardiorenal functions, suggesting that inhibition of DPPIV may attenuate the development and/or progression of HF by mechanisms independent of glucose reduction. Accordingly, a large body of experimental data [ 32 , 33 , 34 , 38 , 87 , 138 ] has demonstrated that genetic deletion or pharmacological inhibition of DPPIV improves cardiovascular outcomes.…”
Section: Dppiv Inhibitors and Hf: Preclinical Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…It is believed that in atherosclerosis the lack of NO bioavailability triggers smooth muscle cell constriction leading to vasospasm in nonobstructive coronary arteries, which leads to myocardial infarction. [33][34][35] Classically, neutrophils and monocytes infiltrations, proinflammatory mediators as well as elevated oxidative stress are implicated the physiopathology of vascular damage, 36 nonetheless, these cascades are still not proven participants of the paradoxical vasoconstriction phenomenon.…”
Section: Discussionmentioning
confidence: 99%